Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

simplify using identities (2a+3b)^2 - (2a-3b)^2

Sagot :

Answer:

24ab

Step-by-step explanation:

Here, the identity A² - B² = (A + B) (A- B) will be used ; A = 2a + 3b, b = 2a - 3b.

=> (2a + 3b + 2a - 3b) (2a + 3b - (2a - 3b))

=> (4a) (2a + 3b - 2a + 3b)

=> (4a) (6b)

=> 24ab

Hope it helps :)